SAT-571 Rare Case of Tocilizumab-Induced Severe Hypertriglyceridemia - Modi, Ankur (J Endocr Soc, 2020)
Tocilizumab (TCZ) is a monoclonal antibody against the IL-6receptor used in the treatment of rheumatoid arthritis (RA). Hypertriglyceridemia is a rare side effect of TCZ, occurring in<1% of cases (1). A 37 year-old woman presented with abdominal pain, nausea and diarrhea. Her past medical history included RA and dyslipidemia; she had no history of diabetes, hypothyroidism, renal disease, alcoholism or recent medication changes. Following failure of other immunosuppressant agents, IV TCZ was initiated. After two and a half years, TCZ formulation was changed to subcutaneous injections for convenience about 6 weeks prior to presentation. Family history included mother with dyslipidemia. Her vital signs were normal on admission with labs remarkable for lipase of 332 and triglycerides (TG) of 5680. Her TG 2months prior to initiating subcutaneous tocilizumab therapy was 1373. CT abdomen demonstrated findings of acute pancreatitis (AP). She was subsequently admitted to the ICU and started on an insulin drip, fibrate, statin and fish oil along with supportive care. TCZ was held. Because her TGs remained severely elevated, she was transferred to our facility for plasmapheresis with subsequent improvement of the same to 768 after two treatments. TCZ was considered the probable etiology of her hypertriglyceridemia with subsequent AP after ruling out other secondary causes. Hereditary hypertriglyceridemia, given her family history, likely contributed to her chronically elevated TG’s. TCZ has been reported to increase TG levels mainly through an increase in VLDL-TG content. TCZ was found to reduce hepatic LDLr expression thus reducing hepatic clearance of TGs and LPL mediated lipolysis of TG-rich lipoproteins (2). Despite the association of TCZ with increased lipid levels, it has a favorable impact on lipid metabolism via improved functionality of HDL-C and no impact in the atherogenic index; patients also experience a favorable response to statin treatment (3). In observational studies, TCZ shows a favorable effect on myocardial infarction compared to other biologic agents for RA, attributed partly to a decrease in lipoprotein(a) levels. Nonetheless, it should be used in caution in those with high cardiovascular risk, especially dyslipidemia (4). 1. Flaig T, Douros A. Tocilizumab-induced pancreatitis:case report and review of data from the FDA Adverse Event Reporting System. Journal of Clinical Pharmacy and Therapeutics 2016, 41:718-721. 2. Strang A, Bisoendial R. Atherosclerosis 229(2013):174-181. 3. Garcıa-Gomez C, Martın-Martınez M. Lipoprotein(a) concentrations in rheumatoid arthritis on biologic therapy:Results from the CARdiovascular inrheuMAtology study project. Journal of Clinical Lipidology (2017) 11:749-756. 4. CastagnéB, Viprey M. Cardiovascular safety of tocilizumab: A systematic review and network meta-analysis. PLoS ONE 14(8):e0220178.